Waste Management Training: Making Table Lamp from Used Plastic Bottles - Awang Eka Novia Rizali; Ariani Ariani (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2020)
The problem of plastic waste in Indonesia has reached a very alarming stage. Waste management is no longer the responsibility of the government and certain parties, but all levels of society. Efforts as simple as anything needs to be done to reduce this buildup of rubbish. Training about using used plastic bottles into sitting lamps is one of the real efforts to educate the community in the village of Banjarsari, Pulosari District, Pandeglang Regency, Banten about the management of plastic waste in their environment. The training method followed by a demonstration became a media of knowledge and skills transfer for the participants consisting of community leaders, housewives, and some youths. Considering the educational background of the target community who have never studied product design principles. It is necessary to give them understanding and basics design knowledge, so the table lamp produced is both functional and aesthetically valuable. The results of this training provide new knowledge and skills, as well as open up insights and motivate them to develop ideas about alternatives for processing waste in their environment.